2021
DOI: 10.1001/jamanetworkopen.2021.18516
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Internet-Delivered vs In-Person Cognitive Behavioral Therapy for Children and Adolescents With Obsessive-Compulsive Disorder

Abstract: Key Points Question Is internet-delivered cognitive behavioral therapy followed by face-to-face treatment for nonresponders a cost-effective alternative to in-person cognitive behavioral therapy alone for children and adolescents with obsessive-compulsive disorder? Findings In this economic evaluation of a randomized clinical trial including 152 children and adolescents with obsessive-compulsive disorder, internet-delivered cognitive behavioral therapy foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…De Boer et al compared e-BMT and in-person BMT in patients with chronic pain and found that the costs of online CBT were EUR 199 lower than in-person BMT [ 85 ]. Similarly, Aspvall et al found that after 6 months of follow-up in children and adolescents with obsessive compulsive disorder, there was a difference of USD 1688 in favor of e-BMT [ 86 ]. Healthcare systems and guidelines should seriously consider implementing e-BMT in the management of patients with musculoskeletal disorders causing chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…De Boer et al compared e-BMT and in-person BMT in patients with chronic pain and found that the costs of online CBT were EUR 199 lower than in-person BMT [ 85 ]. Similarly, Aspvall et al found that after 6 months of follow-up in children and adolescents with obsessive compulsive disorder, there was a difference of USD 1688 in favor of e-BMT [ 86 ]. Healthcare systems and guidelines should seriously consider implementing e-BMT in the management of patients with musculoskeletal disorders causing chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite this effect size, only 27% of youth in ICBT were classified as responders at post-treatment, which is considerably lower than the average response rates across face-to-face CBT trials (i.e., 68%, ( McGuire et al, 2015 ). In a subsequent RCT of stepped-care ICBT, 54% of youth who received ICBT were considered responders at 3 months follow-up, relative to 71% who received face-to-face CBT ( Aspvall et al, 2021 ). While ICBT offers promise in increasing reach, it does not appear to achieve the more favorable response rates observed in face-to-face therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In essence, ICBT mimics traditional in-person CBT in terms of content, the only difference being the mode of delivery ( Hedman et al, 2012 ). The safety, efficacy, durability and cost-effectiveness of ICBT for children and adolescents for OCD have been well established ( Aspvall et al, 2018 ; Lenhard and Andersson, 2017 ; Lenhard et al, 2014 ; Aspvall et al, 2021 ; Lenhard et al, 2020 ; Lenhard et al, 2017 ). A recent study demonstrated non-inferiority of ICBT compared to in-person CBT for OCD when delivered in a stepped-care fashion ( Aspvall and Andersson, 2021 ).…”
Section: Introductionmentioning
confidence: 99%